Математичне моделювання та параметрична ідентифікація теплових процесів з урахуванням апріорної інформації про джерела генерації теплоти - Kostikov A. (General Energy Institute of the National Academy of Sciences of Ukraine, 2014)
The inverse tasks of thermal conductivity are considered, in connection with heat sources identification, applicable both for heat processes optimization at the stage of the different heat-loaded technical objects scheduling, including power industry, and for their diagnostics based on the thermometering data.It is demonstrated that if antecedent information about heat source is missing, this task is inner. As a result of its solution, only the source power distribution through all considered area domain could be found. Herewith, it is impossible to identify subarea of the source itself.Possession of an antecedent information about heat source transfers the task into the class of combined, when it is possible to determine simultaneously both the subarea of heat source in space, and its heat generation power distribution through this subarea. Herewith, antecedent information can be of both geometry and energetic type.As a numerical example, a model inverse task of thermal conductivity is considered, for heat source identification in a stationary one-dimensional case. As antecedent information, the information about simple connected source subarea is used. This fact permits to include the geometry features determining source subarea position into identifiable parameters.